Quelques réflexions sur l’informatique - Parizeau, André (Assurances)

(untitled) (HEC Montréal, 1987)
In his article, Mr. André Parizeau expounds on the elements of a well-managed project: a clearly defined commitment from all parties concerned, the proper planning, from the outset, of all its phases, a judicious analysis of the choices to be made throughout the project and, finally, effective communication between the various groups involved.